Acute Effects of Three Different Meal Patterns on Postprandial Metabolism in Older Individuals with a Risk Phenotype for Cardiometabolic Diseases: A Randomized Controlled Crossover Trial. Issue 9 (15th April 2020) - Schönknecht, Yannik B.; Crommen, Silke; Stoffel‐Wagner, Birgit; Coenen, Martin; Fimmers, Rolf; Holst, Jens J.; Simon, Marie‐Christine; Stehle, Peter; Egert, Sarah
Abstract : Scope: The aim of this study is to investigate acute postprandial responses to intake of meals typical for Mediterranean and Western diets. Methods: In a randomized crossover design, overweight and obese participants with a risk phenotype for cardiometabolic diseases consumed three different isoenergetic meals: Western diet‐like high‐fat (WDHF), Western diet‐like high‐carbohydrate (WDHC), and Mediterranean diet (MED) meal. Blood samples are collected at fasting and 1, 2, 3, 4, 5 h postprandially and analyzed for parameters of lipid and glucose metabolism, inflammation, oxidation, and antioxidant status. Results: Compared to MED and WDHF meals, intake of a WDHC meal results in prolonged and elevated increases in glucose and insulin. Elevations for triglycerides are enhanced after the WDHF meal compared to the MED and the WDHC meal. Glucagon‐like peptide‐1 and interleukin‐6 increase postprandially without meal differences. Apart from vitamin C showing an increase after the MED meal and a decrease after WDHF and WDHC meals, antioxidant markers decrease postprandially without meal differences. Plasma interleukin‐1β is not affected by meal intake. Conclusions: Energy‐rich meals induce hyperglycemia, hyperlipemia, an inflammatory response, and a decrease in antioxidant markers. A meal typical for the Mediterranean diet results in favorable effects on glycemic, insulinemic, and lipemic responses. Abstract : The acute impact of three different meal patterns (Western diet‐like high‐fat vs. Western diet‐like high‐carbohydrate vs. Mediterranean diet) on postprandial metabolic, inflammatory, and oxidative events are examined in participants with cardiovascular diseases (CVD) risk. Attenuating the postprandial stress response events through specific nutritional interventions seems to be a promising approach to decrease the susceptibility of the development of CVD.